Trabeculectomy with concurrent intravitreal bevacizumab in neovascular glaucoma - Sardar M Khan; Aparna Rao (Indian Journal of Ophthalmology, 2024)
Purpose: To evaluate the clinical efficacy of concurrent intravitreal bevacizumab (IVB) injection with trabeculectomy with mitomycin-C (MMC) in neovascular glaucoma (NVG). Methods: Patients with NVG who underwent trabeculectomy with concurrent IVB (group 1) and those who underwent IVB sequentially, followed by trabeculectomy with MMC (group 2) in 1–2 weeks between January 2021 and August 2022, were included in this retrospective hospital-based study. The need for medications for intraocular pressure (IOP) control at 6 months in the two groups was the primary outcome measured and compared between the groups. The association of the need for medications postoperatively with clinical variables was assessed using stepwise multivariate regression statistics. Results: We finally included 40 patients (n = 12 in group 1, n = 28 in group 2) with no significant differences in presenting age between groups. The IOP at 1 day and 1 week were not significantly different between groups though the IOP at 1, 3, and 6 months. IOP was lower in group 1 eyes with the 6-month IOP, being significantly lower in group 1, P = 0.05. Three eyes in group 1 and 11 eyes in group 2 required anti-glaucoma medications in the postoperative period. Multivariate regression identified preoperative IVB >3 (β =0.7, P < 0.001) and recurrent vitreous hemorrhage (β = 0.7, P = 0.004) as prognostic factors (R2 = 40.6%) determining the need for anti-glaucoma medication (AGM) postoperatively in both groups. Conclusion: Concurrent IVB with trabeculectomy with mitomycin-C is a feasible alternative in patients with NVG with refractory high-presenting IOP. This may serve to address raised IOP as well as retinal ischemia, thereby improving surgical success rates in the most challenging NVG cases.